Changes of serum miR-221 and miR-145 levels with papillary thyroid carcinoma and their relationship with invasive activity - Zhu, Zheng-Cai; Li, Tao; Yao, Tian-Qi; Bi, Jing-Cheng; Jiao, Liang-He (Cellular and Molecular Biology, 2022)
This study aimed to investigate the expression of miR-221 and miR-145 in papillary thyroid carcinoma, and the effect of miR-221 and miR-145 on the invasion ability of thyroid cancer cells and its mechanism. For this purpose, 120 patients with thyroid nodules were divided into the observation group (PTC) of 43 cases and the control group (benign nodules) of 42 cases according to postoperative pathological diagnosis. Total RNA was extracted from serum samples of all patients, and the expression levels of miRNA-145 and miR-221 were detected by fluorescence quantitative PCR. The expression of two kinds of miRNAs in the groups was compared, and their correlation was analyzed. The results showed that the expression of miRNA-145 in thyroid cancer tissues was lower than that in paired adjacent normal tissues (P < 0.001). The expression of miRNA-221 in thyroid cancer tissues was higher than that in paired adjacent normal tissues (P < 0.001). The proliferation and migration ability of miRNA-145 cells were significantly decreased (P < 0.01). The expression of miRNA-221 was up-regulated, and the proliferation and migration ability of cells was significantly enhanced (P < 0.05). High expression of miRNA-145 can inhibit cell proliferation and migration and promote apoptosis, while high expression of miRNA-221 will promote cell proliferation and migration and enhance the invasion ability of cancer cells. In general, the expression of miRNA-22l in serum of PTC patients is significantly up-regulated, while the expression level of miR-145 is down-regulated, which can be used as effective indicators to judge the biological activity of the tumor, and the combined detection of the two can significantly enhance the diagnostic value of PTC. Upregulation of miR-145 inhibits PTC cell proliferation; arrests cell cycle and promotes apoptosis miR-145 may play an important role as a tumor suppressor gene.